Etiopathological Factors Associated with Gynecomastia Patients Seeking Surgical Correction in the South Indian Population - L.S. Sreelesh; Sheeja Rajan; A. K. Anu (Indian Journal of Plastic Surgery)
Background Although several medical conditions are associated with gynecomastia, around 60% of cases are idiopathic. The role of endocrine testing in idiopathic gynecomastia is controversial. This study was done to determine the etiological and lifestyle factors associated with different grades of gynecomastia. Patients and Methods This was a descriptive study conducted at the department of plastic surgery in a tertiary care hospital in South India between January 2014 and December 2016, among the patients seeking corrective surgery for gynecomastia. Results A total of 73 patients were included in the study with a mean age of 22.56 years. The majority of the patients displayed Simon's Grade IIa gynecomastia (56.2%). The etiological factors identified in this study were hormonal abnormalities (47.95%), hypogonadism (2.7%), and drug intake (1.4%). The most common hormonal abnormality discovered was high estradiol values (15.1%) followed by decreased testosterone levels (13.7%). The chi-squared test revealed no statistically significant relationship between the hormonal values, type of food, body mass index (BMI), or physical activity and the grades of gynecomastia. Conclusion Most of the patients (50.68%) in our study had idiopathic gynecomastia. The most common hormonal abnormality detected was high estradiol values. No correlation was found between the hormonal values, type of food, BMI, or physical activity and the grades of gynecomastia.